Cbf1 regulates chromatin remodelling of the Saccharomyces cerevisiae genome at multiple binding sites - Garduño, B; Garduño, Bertha Veroni?a (1999)
The centromere binding factor 1, Cbf1, of Saccharomyces cerevisiae is a bHLH/ZIP protein which has been described as a determinant of specific chromatin structures and as a tethering factor for activators of transcription at the promoters of genes of the Methionine Biosynthesis Pathway. Deletion mutants show various phenotypes, among them methionine auxotrophy, an increased rate of chromosome loss, modifications in the growth rate and modification of the chromatin structure at MET genes. Meiosis competence also becomes greatly reduced in cbf1 cells. The sequence motif (RTCACRTG) to which Cbf1p binds is found at multiple loci through the yeast genome. This thesis shows that the chromatin structure is reorganised at multiple Cbf1p binding sites in vivo, when yeast cells are starved to enter meiosis. Extensive remodelling occurs at the MET16, MET17(25), DRS2 and GDH3 loci and at the YAL060W open reading frame, as detected by in vivo digestion of chromatin with micrococcal nuclease and indirect end-labelling. The same kind of analysis showed that the remodelling of chromatin at Cbf1p binding sites is not specific for meiosis, it occurs also in similarly starved haploid cells. The lack of methionine is a key trigger of these changes. This reorganisation of chromatin is dependent on Cbf1p, since starved cbf1 cells do not display any modification in nuclease accessibility patterns at or around Cbf1p binding sites. Mutational analysis revealed that a negative charge at a putative phosphorylation site (serine residue 226) and the DNA-bindmg activity of Cbf1p are both required for the chromatin reorganisation to occur in response to starvation. CBF1 mutants which do not reorganise chromatin were also shown to be unable to enter meiosis, suggesting that the remodelling of chromatin at multiple Cbf1p binding sites may be required to enter pre-meiotic DNA replication, since such cells arrest before the initiation of this process. In summary, the results presented in this thesis are compatible with a model in which Cbf1p plays an active role as part of a mechanism sensing the nutrient availability and regulates the reorganisation of chromatin, at multiple loci through the yeast genome, in response to starvation conditions.